The Effect Of Differentiation Strategy On Consumer Loyalty In Ud Trans Jaya Kasokandel Majalengka District - Neneng Ratnasari; Arif Rohman Hakim (Budapest International Research and Critics University, 2022)
The Effect of Differentiation Strategy on Consumer Loyalty at Ud Tran Jaya Kasokandel, Majalengka Regency. Ud Tran Jaya Kasokandel is a retail business in Majalengka Regency that seeks to increase consumer loyalty for the company's UD (trading business) Tras Jaya Kasokandel is a retail business in Majalengka Regency that strives to increase consumer loyalty for the company's long-term survival. UD Tran Jaya Kasokandel has always made efforts to increase consumer loyalty; among them is the differentiation strategy that UD Tran Jaya Kasokandel always develops to bind consumers. The problem of this research is to find out if there is an influence of differentiation strategy on consumer loyalty. The population of this study was all consumers of Ud Tran Jaya Kasokandel with sampling technique using random sampling using the slovin formula to produce 96 people. The nature of this research is descriptive and verification. The data analysis methods are regression analysis, correlation, determination, and t-test. Based on the analysis results, there is an influence between the differentiation strategy and consumer loyalty; this is proven through hypothesis testing using the t-test so that it can be count is greater than t table (9, 8724 > 1.66123). The correlation value between differentiation strategy and consumer loyalty at Ud Tran Jaya Kasokandel Majalengka Regency based on research data is 0.7103. So the relationship between differentiation strategy variables and consumer loyalty at Ud Tran Jaya Kasokandel Majalengka Regency is included in the category of a strong relationship. The contribution of differentiation strategy to consumer loyalty is 50,46%, or it can be said that the variance that occurs in the consumer loyalty variable (Y) 50,46 % is determined by the variance that occurs in the differentiation strategy variable (X). The rest, amounting to 49%, factors outside this study determine 54%. The regression equation is: Y = 1, 11 + 0,41 X. It means: b is positive, namely 1,11, meaning that X positively affects Y. The regression coefficient of 0,41 states that every increase (because b is +) 1 unit of differentiation strategy will increase consumer loyalty by 0,41 units.